Land use of catchment area of Lake Łódzko-Dymaczewskie, Lake Dębno and Lake Trześniowskie in Poland - Michał Woszczyk; Mikołaj Majewski; Carsten J Schubert; Robert van Geldern (PANGAEA, 2025)
The dataset contains systematic observations of water parameters (t [°C], conductivity [μS·cm-1], pH, oxygen [mg·L-1], oxygen saturation [%], ORP [mV], TOC [mg·L-1], DOC [mg·L-1], chlorides [mg·L-1], sulphates [mg·L-1], nitrates [mg·L-1]), stable isotope composition of DIC (δ13CDIC; extperthousandV-PDB) and trace gas (CH4 [nmol·L-1], N2O [nmol·L-1], H2S [mg·L-1]) distribution in the water columns of three inland freshwater lakes in Poland (central-eastern Europe). The observations were collected monthly between July 2019 and July 2020 as well as quarterly between July 2021 and September 2022 from Lake Łódzko-Dymaczewskie, Lake Dębno and Lake Trześniowskie. The lakes show considerable variability of trophic conditions from mesotrophic (L. Trześniowskie) to highly eutrophic/hypetrophic (L. Łódzko-Dymaczewskie) as well as catchment morphology and land use. The bathymetric data and catchment characteristics for each lake are also provided in our database. The hadrochemical measurements and sampling was done in the deepest site in each lake using standard methods. H2S was determined spectrophotometrically on-site and the CH4 and N2O were analysed in the laboratory using gas chromatography. SO42-, Cl- and NO3- were determined with ion chromatography, HCO3- was manually titrated with HCl with regard to dye and DOC/TOC was analysed with TOC analyzer. Detailed methodology was described by Woszczyk & Schubert (2023). Creation of this dataset aimed at providing the first comprehensive set of information on the occurrence and formation of trace gases in Polish lakes. Special focus was put on potent greenhouse gases (CH4 and N2O), which are expected to increase owing to the ongoing climate warming and accompanying environmental changes (Bartosiewicz et al. 2019). Such database is to extend the existing datasets from northern and western Europe by including observations from aquatic systems in which the GHG data was missing altogether. In addition, to the best of our knowledge, our database is one of the very few, to provide the limnological and biogeochemical community with systematic H2S data. So as GHG, the accumulation of this highly toxic gas in lake waters is projected to accelerate in the following decades. Our data can be used for calculating accumulation rates in water columns as well as to assess atmospheric emissions from lakes. Catchment and hadrochemical data can be used to decipher processes behind production and release of the trace gases from lakes to the ambient air.
In: Woszczyk, M et al. (2025): Trace gases (CH4, N2O, H2S) in the water columns from Lake Łódzko-Dymaczewskie, Lake Dębno and Lake Trześniowskie in Poland [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.977483